SAT0466 Serum vitamin d deficiency is associated with active renal disease in systemic lupus erythematosus. (12th June 2018) - Park, Y.-J.; Baek, I.-W.; Kim, K.-J.; Kim, W.-U.; Cho, C.-S.
Abstract : Objectives: 25-hydroxyvitamin D (25(OH)D) deficiency is common in systemic lupus erythematosus (SLE) as well as chronic kidney disease. In this study, we investigated the association of 25(OH)D deficiency and renal involvement in SLE patients. Methods: Two hundred seventy-two SLE patients and 138 control subjects were enrolled; 102 patients with active nephritis, 42 patients with inactive nephritis, and 128 patients with non-renal disease. Serum 25(OH)D levels were measured, and clinical and laboratory data were obtained from medical records. Results: Mean serum 25(OH)D levels were significantly lower in SLE patient than control subjects (19.6 ng/ml versus 21.7 ng/ml, p=0.006). Out of 272 patients, 61.8% were vitamin D deficient (defined as <20 ng/ml). Patients with active nephritis had lower serum 25(OH)D levels (16.9 ng/mL) than patients with inactive nephritis (20.2 ng/mL) and without nephritis (21.5 ng/mL) (p=0.030, p<0.001), but there was no difference between the inactive nephritis and non-renal disease. Moreover, serum 25(OH)D levels were positively correlated with complement C3 (γ=0.135, p=0.026) and C4 (γ=0.159, p=0.009), but inversely with anti-dsDNA antibody level (γ=−0.156, p=0.010). Analysis of receiver operating characteristic curve for differentiating active nephritis and non-renal disease revealed an area under the curve (AUC) of 0.676, which is better than those of anti-dsDNA antibody (AUC=0.585, p=0.038) and complement C3 (AUC=0.509, p=0.001), C4 (AUC=0.538, p=0.008). Conclusions: Vitamin D is deficiency is more common in SLE patients with active nephritis, and its level could be a potential marker for active renal disease in SLE. A prospective cohort study is needed to further elucidate the causal relationships over time. Disclosure of Interest: None declared